Frequency of Sustained Virologic Response in Hepatitis C Positive, Treatment Naïve Patients on Sofosbuvir and Daclatasvir - Shah, Islam; Munib, Nayab; Badshah, Aliena; Mohammad, Wazir (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To measure the frequency of sustained virologic response in Hepatitis C positive, treatment naïve patients on Sofosbuvir and Daclatasvir. METHODOLOGY This descriptive study was conducted in the Department of Medicine, Khyber Teaching Hospital Peshawar from 15th May 2020 to 14th November, 2020. A sample size of 93 was calculated by using sustained virologic response in 96% patients using Sofosbuvir and Daclatasvir with the confidence level as 95% and 4% margin of error under WHO formula for sample size determination in health studies. Consecutive non probability sampling technique was used in the study. RESULTS Ninety Three treatment naïve hepatitis C patients were included in the study containing 53 males (57%) and 40 females (43%) with mean age of 43 + 0.23. 84 (90%) patients were in Child A class according to Child Pugh score. Overall 89 (95.7%) patients showed sustained virologic response following 12 weeks treatment of naïve HCV patients with combination of sofosbuvir and daclastavir. 5 patients developed side effects to the drugs; 2 patients developed anemia with one patient having anemia severe enough to require blood transfusion. 4 patients did not respond to the treatment regime in terms of sustained virologic response for 12 week treatment and were continued for 24 weeks on the same regime. CONCLUSION This study concludes that combined sofosbuvir and daclatasvir for 12 weeks appear to have sustained virologic response in treatment naïve HCV patients. Child score has statistically significant correlation to sustained virologic response with Child A class showing SVR in all patients. Patients in Child class C did not show SVR. Thrombocytopenia has direct and negative affect on SVR.